Highly specific targeted mutagenesis in plants using Staphylococcus aureus Cas9 - Kaya, Hidetaka (Sci Rep, 2016)
The CRISPR/Cas9 system is an efficient and convenient tool for genome editing in plants. Cas9 nuclease derived from Streptococcus pyogenes (Sp) is commonly used in this system. Recently, Staphylococcus aureus Cas9 (SaCas9)-mediated genome editing was reported in human cells and Arabidopsis. Because SaCas9 (1053 a.a.) is smaller than SpCas9 (1368 a.a.), SaCas9 could have substantial advantages for delivering and expressing Cas9 protein, especially using virus vectors. Since the protospacer adjacent motif (PAM) sequence of SaCas9 (5′-NNGRRT-3′) differs from that of SpCas9 (5′-NGG-3′), the use of this alternative Cas9 nuclease could expand the selectivity at potential cleavage target sites of the CRISPR/Cas9 system. Here we show that SaCas9 can mutagenize target sequences in tobacco and rice with efficiencies similar to those of SpCas9. We also analyzed the base preference for ‘T’ at the 6th position of the SaCas9 PAM. Targeted mutagenesis efficiencies in target sequences with non-canonical PAMs (5′-NNGRRV-3′) were much lower than those with a canonical PAM (5′-NNGRRT-3′). The length of target sequence recognized by SaCas9 is one or two nucleotides longer than that recognized by SpCas9. Taken together, our results demonstrate that SaCas9 has higher sequence recognition capacity than SpCas9 and is useful for reducing off-target mutations in crop.